Congo : the epic history of a people - Van Reybrouck, David; Garrett, Sam (New York, NY : Ecco, an imprint of HarperCollins Publishers, 2015)
Van Reybrouck reviews some of the most dramatic episodes in Congolese history -- from the slave trade to the ivory and rubber booms; from the arrival of Henry Morton Stanley to the tragic regime of King Leopold II; from global indignation to Belgian colonialism; from the struggle for independence to Mobutu's brutal rule; and from the world famous Rumble in the Jungle to the civil war over natural resources that began in 1996 and still rages today.
New spirits: Central Africa draws the attention of East and West, 1870-1885 -- "Diabolical filth": Congo under Leopold II, 1885-1908 -- The Belgians set us free: The early years of the colonial regime, 1908-1921 -- In the stranglehold of fear: Growing unrest and mutual suspicion in peacetime, 1921-1940 -- The red hour of the kickoff: The war and the deceptive calm that followed, 1940-1955 -- Soon to be ours: A belated decolonization, a sudden independence, 1955-1960 -- A Thursday in June -- The struggle for the throne: The turbulent years of the First Republic, 1960-1965 -- The electric years: Mobutu gets down to business, 1965-1975 -- Toujours servir: A marshal's madness, 1975-1990 -- The death throes: Democratic opposition and military confrontation, 1990-1997 -- Compassion, what is that?: The great war of Africa, 1997-2002 -- t
Translation of: Congo : een geschiedenis.
Includes bibliographical references (pages 597-618) and index.
Keywords: History -- Africa -- Central; Political science -- Genocide & War Crimes; Political science -- Imperialism; Congo (Democratic Republic) -- History; Congo (Democratic Republic); Congo (Democratic Republic.); History